30.6k views
0 votes
If x = 2 and y = 4, then (2x + 3y) ÷ 4 - 2 =

User Axle
by
4.8k points

2 Answers

2 votes

Answer:

2

Explanation:

(2x+3y)÷4-2=(2(2)+3(4)÷4-2

2*2=4+12/4-2

3*4=12

4+12/4-2

16/4

4-2

2

User Cody Casterline
by
5.5k points
1 vote

Answer:

2

Explanation:

Remember to follow PEMDAS, the order of operation.

PEMDAS =

Parenthesis

Exponents (& roots)

Multiplications

Division

Addition

Subtraction

First, plug in 2 for x, and 4 for y

(2(2) + 3(4))/4 - 2

Simplify:

2 * 2 = 4

3 * 4 = 12

4 + 12 = 16

16/4 = 4

4 - 2 = 2

2 is your answer.

~

User Tags
by
5.5k points